Determination the Number of Packing Operators Using Work Sampling Method - et. al., Yani Iriani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
X is a manufacturing company in Indonesia that produces building materials such as Autoclave Aerated Concrete (AAC) lightweight concrete bricks, wall panels and floor panels. In the production process, this company is still experiencing several obstacles, one of which is in achieving the number of production targets at the Dept. Packing. Based on company data in the 2018 period the achievement of production targets at the Dept. Packing only reached 50.20% of the target requested by the company. One of the causes of not achieving the production target is the number of workers who are not balanced with the workload, which eventually causes a queue to build up at the Dept. Packing. The buildup that occurred at the Dept. This packing hinders the processes that were in the previous process section so that the production process does not run smoothly. To improve this situation, it is proposed to take work measurements using the Work Sampling method. This study aims to determine the standard time and the number of operators required. Work Sampling is a technique for making a large number of observations on the work activity of an operator for a randomly taken interval of time to one or more operators in a working or unemployed state. From the results of data processing, the standard time for operator A is 0.25 minutes, the standard time for operator B is 0.28 minutes, and the standard time for the operator is 0.25 minutes. Based on the standard time, the current operator capacity can only work 1,890 concrete bricks per day out of the 3,780 concrete bricks targeted by the company. Proposed comparison by adding the number of operators in each packing process from 3 operators to 6 operators. With this proposal, it can balance the workload of operators and increase the number of production targets demanded by the company, from 50.20% to 77.55%.